Integrated Social Safety Nets: Building Community Resilience for Sustainable Food Security - Ekiru, Mark; Mulwa, Angeline; Kyalo, Dorothy (University of Nairobi, 2021)
In Kenya, several social safety net programmes have been initiated to support lives and livelihoods and to enhance resilience to shocks. The existing social safety net programmes in the Country include the Hunger Safety Net Programme, Orphans and Vulnerable Children Cash Transfer, Older Persons Cash Transfer Programme, People Living with Severe Disabilities Cash Transfer Programme, and the Urban Food Subsidy Cash Transfer Programme (NGEC, 2014). These are per Article 21 of the Constitution of Kenya, which puts forward that it is the responsibility of the State to ensure that the economic and social rights of citizens are met (Constitution of Kenya, 2010). Government ownership of social safety net initiatives has shown some hope for the implementation of the programmes. However, the sustainability of the programmes is a major worry due to their dependence on donors' funding and technical support (Barrientos and Hume, 2009). Despite the approval of the National Social Protection Policy in 2011, Kenya has continued to record a high incidence of poverty coupled with food insecurity and malnutrition, made worse by disasters and stresses (Ministry of State for Planning and National Development, 2012). The purpose of this study, therefore, focused on the current social safety nets in Turkana County, primarily on the use of cash transfer programmes and its role in community resilience and food security. Turkana County is among the semi-arid lands of Kenya prone to drought and suffers from historical marginalization, struggling with weak infrastructure as well as high rates of illiteracy (OPM 2011). The County is among the four ASAL counties where the Hunger Safety Net Programme (HSNP) was piloted as a viable solution to the eradication of poverty, hunger and malnutrition in the longer term.